Efektivitas Pengolahan Limbah Fisik (Padat Dan Cair) Dengan Menggunakan Teknologi Inovatif - Gilang Nur Affandi; Putu Cahya Gita Berlianti; Novia Reyhan Ramadhania; Ryan Syehan Abi Shawaaba; Denny Oktavina Radianto (JURNAL WILAYAH, KOTA DAN LINGKUNGAN BERKELANJUTAN, 2024)
Background: Management of physical waste (solid and liquid) is an important aspect in maintaining environmental sustainability. In recent years, innovative technology has become a major focus in efforts to increase the effectiveness of physical waste management. The aim of this research is to examine the effectiveness of physical waste processing using innovative technology for each type of waste. Method: The research method that will be used in this research includes a literature review. The research method that will be used in this research is a key step to test and evaluate the effectiveness of innovative technology in physical waste processing. Results: Physical waste, such as plastic, electronics, and paper, has become an increasing global environmental problem. The impacts include soil, water and air pollution as well as human health risks. Effective physical waste management is important to reduce its negative impacts. Solutions include public education, government-industry collaboration on policy, and technological innovation. With good collaboration, it is hoped that effective solutions can be created to maintain environmental sustainability and human health. Innovative technologies in solid and liquid waste management provide advantages such as solutions to environmental problems, increased efficiency, and the creation of new, better products. However, challenges such as high investment costs, inadequate infrastructure and limited regulation need to be overcome. To overcome these challenges, cooperation between government, companies, academics and society is needed.